1992
DOI: 10.1007/bf00196248
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels from the plasma membrane of rye roots characterized following incorporation into planar lipid bilayers

Abstract: Plasma membrane was purified from roots of rye (Secale cereale L. cv. Rheidol) by aqueous-polymer two-phase partitioning and incorporated into planar bilayers of 1-palmitoyl-2-oleoyl phosphatidylethanolamine by stirring with an osmotic gradient. Since plasmamembrane vesicles were predominantly oriented with their cytoplasmic face internal, when fused to the bilayer the cytoplasmic side of channels faced the trans chamber. In asymmetrical (cis:trans) 280∶100 mM KCl, five distinct K(+)-selective channels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Although TEA' inhibits the majority of known plant K+ channels (Bentrup, 1990), some TEA+-insensitive K+ channels have been reported, e.g. the Ca2+-dependent K+ channel found in Haemanthus and C h i a endosperm (Stoeckel and Takeda, 1989) and the plasma membrane 49 pS channel from rye roots (White and Tester, 1992). The failure of the LATS to respond to TEAf in Chlamydomonas may be related to the structure and characteristics of this low-affinity transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Although TEA' inhibits the majority of known plant K+ channels (Bentrup, 1990), some TEA+-insensitive K+ channels have been reported, e.g. the Ca2+-dependent K+ channel found in Haemanthus and C h i a endosperm (Stoeckel and Takeda, 1989) and the plasma membrane 49 pS channel from rye roots (White and Tester, 1992). The failure of the LATS to respond to TEAf in Chlamydomonas may be related to the structure and characteristics of this low-affinity transporter.…”
Section: Discussionmentioning
confidence: 99%
“…These channels have been observed ubiquitously in all root cell types studied. When incorporated into planar lipid bilayers, a P Cs \P K of 0.85 was estimated from measurements of E rev under bi-ionic conditions for the VIC channel from rye roots (White & Tester, 1992). In general, VIC channels have a probability of being open (P o ) of 0.65-0.80 at voltages more positive than k120 mV, but opening might decline at extreme negative voltages (White, 1997(White, , 1999Davenport & Tester, 2000).…”
Section: Voltage-insensitive Cation (Vic ) Channelsmentioning
confidence: 99%
“…Cation permeation through the VIC channel was modelled by using an energy-barrier model derived for the VIC channel in the plasma membrane of rye roots (White, 1997(White, , 1999, supplemented with the free-energy profiles for Cs + permeation deduced from data presented by White & Tester (1992). This model assumes single-file permeation through the pore of VIC channels, and places two cation-binding sites within the pore.…”
Section: Predicted Cs + Influx Through Cation Channelsmentioning
confidence: 99%
“…There are two known TEA 1 -sensitive, K 1 -transporting systems in the Arabidopsis plasma membrane: hyperpolarization-and depolarization-activated K 1 channels or, in other terminology, K 1 inward and outward rectifiers, respectively (Maathuis and Sanders, 1995;Véry and Sentenac, 2003). A contribution from the third system-voltage-insensitive, outwardly directed NSCCs-cannot be completely ruled out, although White and Tester (1992) showed that TEA 1 permeates but does not block root NSCCs. Since Na 1 -induced, TEA 1 -sensitive K 1 efflux was not affected in akt1 plants, we can rule out the idea that this efflux was caused by Na 1 block of K 1 influx Figure 8.…”
mentioning
confidence: 99%